Socket preservation using autogenous bone graft and dentin autograft after surgical removal of impacted mandibular third molar - A split-mouth study design - Priyanka Sinder Gupta; Prashant Ashok Punde; Kumar Nilesh; Pankaj Bajirao Patil; Shrenik Chouradiya; Riddhi Hemant Mahalle (Wolters Kluwer Medknow Publications, 2022)
Introduction: In our study, we have compared the efficacy of dentin bone graft for purpose of ridge preservation and have compared it with autogenous bone graft (ABG). A total of 15 patients were included in this study requiring extraction of bilaterally impacted third molar. On the one side, the socket was filled with processed dentin graft prepared after extraction of the third molar, and on the other side, the socket was filled with ABG harvested from external oblique ridge. The two were compared on the basis of various soft tissue and hard tissue parameters. Aims: This study aimed to evaluate and compare the efficacy of the dentin autograft with ABG for preservation of socket defect after removal of mandibular third molars clinically and radiographically. Materials and Methods: A total of 15 patients were included undergoing extraction for bilaterally impacted third molar. The socket on one side after extraction was filled with processed dentin from the same extracted tooth, and the other side of the socket was filled with ABG harvested from the external oblique ridge. Results: It was seen that dentin graft had the regenerative properties and showed potential for ridge preservation. Conclusions: Ridge preservation is essential for placement of implant and other prostheses. Preservation of ridge immediately after extraction bypasses the need for extensive ridge augmentation procedure. Hence, dentin graft can be used for this purpose as it has potential for bone regeneration.